2009
DOI: 10.1186/1471-2180-9-142
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the suitability of antibiotic resistance markers and the indirect ELISA technique for studying the competitive ability of selected Cyclopia Vent. rhizobia under glasshouse and field conditions in South Africa

Abstract: Background: Symbiotic N2 fixation in legumes is constrained by many factors, including the paucity of suitable soil rhizobia To maximise growth of legume species therefore often requires the application of effective rhizobia as inoculants. But where native strains out-compete introduced rhizobia for nodule formation, it is important that the competitiveness of selected strains is tested in the field and glasshouse prior to their recommendation as commercial inoculants. However the methodology for strain identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…An alternative may be the choice of a natural selection, such as for antibiotic resistance; however, enrichment in a strain tolerant to high antibiotic doses is also not desirable for the environment, because this trait may be dispersed by horizontal gene transfer, and in addition, several reports also indicate that selection for resistance to high antibiotic concentration may yield strains with diminished competitiveness (Lochner et al, 1989;Spriggs & Dakora, 2009;Thomas-Oates et al, 2003). Therefore, if this method is chosen, a careful assessment of symbiotic and competitive abilities of the antibiotic-resistant derivatives must be carried out before employing them in competition studies (López-García et al, 2002;Spriggs & Dakora, 2009). Intrinsic antibiotic resistance to low doses (without enrichment by selection) may be used but this method is not so efficient to distinguish an indicator strain in a population (Spriggs & Dakora, 2009).…”
Section: Methods Employed To Study Competition For Nodulationmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative may be the choice of a natural selection, such as for antibiotic resistance; however, enrichment in a strain tolerant to high antibiotic doses is also not desirable for the environment, because this trait may be dispersed by horizontal gene transfer, and in addition, several reports also indicate that selection for resistance to high antibiotic concentration may yield strains with diminished competitiveness (Lochner et al, 1989;Spriggs & Dakora, 2009;Thomas-Oates et al, 2003). Therefore, if this method is chosen, a careful assessment of symbiotic and competitive abilities of the antibiotic-resistant derivatives must be carried out before employing them in competition studies (López-García et al, 2002;Spriggs & Dakora, 2009). Intrinsic antibiotic resistance to low doses (without enrichment by selection) may be used but this method is not so efficient to distinguish an indicator strain in a population (Spriggs & Dakora, 2009).…”
Section: Methods Employed To Study Competition For Nodulationmentioning
confidence: 99%
“…Therefore, if this method is chosen, a careful assessment of symbiotic and competitive abilities of the antibiotic-resistant derivatives must be carried out before employing them in competition studies (López-García et al, 2002;Spriggs & Dakora, 2009). Intrinsic antibiotic resistance to low doses (without enrichment by selection) may be used but this method is not so efficient to distinguish an indicator strain in a population (Spriggs & Dakora, 2009). Other methods, which do not involve any manipulation of the strains, are antibody or DNA labelling.…”
Section: Methods Employed To Study Competition For Nodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These tools include the use of antibiotic resistance markers, enzyme linked immunosorbent assay (ELISA) (Spriggs and Dakora 2009), DNA-based methods [polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) (Krasova-Wade et al 2006), enterobacterial repetitive intergenic consensus (ERIC) PCR (Ampomah et al 2008), quantitative polymerase chain reaction (qPCR) (Checcucci et al 2016) and fluorophore-enhanced, repetitive, extragenic, and palindromic-PCR (HFERP) DNA fingerprinting (Wongphatcharachai et al 2015)] and proteomic profiling by matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry (MS) (Ziegler et al 2012(Ziegler et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important that the competitiveness of selected rhizobial strains is tested in the field prior to recommending their use as commercial inoculants. In order to estimate the occupancy and identify strain inside nodules, Spriggs and Dakora (2009) reported that the ELISA technique is highly specific, reproducible, and commonly used to detect rhizobial strains directly from nodules. Additionally, the method is sensitive, can detect antigens in small nodules, uses small quantities of reagents, is relatively quick, and permits the rapid screening of large nodule samples.…”
Section: Introductionmentioning
confidence: 99%